PENINGKATAN PRODUKTIVITAS INDUSTRI KACANG METE MELALUI PENGEMBANGAN OTOMASI OVEN MULTI RAK - Didik Ariwibowo; Sutrisno Sutrisno; Mohamad Endy Yulianto; Juli Mrihardjono (Jurnal Pengabdian Vokasi, 2022)
The activities of Iptek Bagi Desa Binaan (IBDU) UNDIP tahun 2021 aims to increase the productivity of the Tiga Saudara cashew nut small scale industry  partner through introduction of a thermocontrolled multi-rack oven, so that quality of cashew nuts would be uniform, shorter processing time, and therby increasing income. The activity of multi-rack oven development was carried out by the Community Service Team of LPPM UNDIP through Iptek Bagi Desa Binaan (IBDU) program. The program was carried out instages including: i) oven design, ii) oven manufacturing, dan iii) functional and adaptation testing, dan iv) oven operation. The purpose of adaptation test is to operate the oven in relevance environment, whereas operationalization was to operate in an actual environment. Implementation of IBDU activites carried out by by the Community Service Team of LPPM UNDIP through the introduction of oven has had positive impact on Tiga Saudara’s partner. The thermocontrolled multi-rack oven has shown that the performance of these equipment is better, able ti produce uniform cashew nut quality so that productivity increases